Oral health knowledge, attitudes, and practices among female public health and nutrition university students in Qatar - Amal Elwadia; Aisha Naeem; Shajitha Thekke Veettil; Nikki Orquia; Diana Alsayed Hassan; Paul Amuna; Alaa Daud (Frontiers Media S.A., 2024)
ObjectivesThe present study aimed to determine oral health (OH) related knowledge, attitudes, and practices among Public Health (PH) and Nutrition (NU) students at Qatar University.MethodA cross-sectional study was conducted using a pre-validated questionnaire comprising 36 items covering demographics, knowledge, attitudes and perception of oral health practices. Data were analyzed descriptively (means, standard deviations, proportions) and inferentially using statistical tests including t-tests for comparing means, and chi-square tests for examining associations between categorical variables.ResultsA total of 112 female undergraduate students participated, including 41 from PH and 71 from NU programs (response rate for both courses = 59.5%). The mean age was 21.8, while 23% were Qataris and 77% non-Qataris. Overall, students demonstrated good knowledge of OH (67.65%), with the PH group scoring higher (70.7%) than NU (65.35%). Knowledge regarding dental plaque was low for both groups (31.0%). Attitudes toward OH varied among participants. Most students reported practicing brushing with fluoridated toothpaste and demonstrated high knowledge regarding the association between poor OH and general health (95%).ConclusionOverall, PH and NU undergraduate students exhibited relatively good knowledge of OH, however, demonstrated a range of attitudes and practices, including suboptimal ones. Integration of OH education into the PH and NU curriculum is warranted, along with enhanced interprofessional education to promote self-awareness and improve patient oral health outcomes.